1999
DOI: 10.1021/ie970581+
|View full text |Cite
|
Sign up to set email alerts
|

Probing Structure−Property Relationships in Third-Order Nonlinear Optical Polymers:  Third Harmonic Generation Spectroscopy and Theoretical Modeling of Systematically Derivatized Conjugated Aromatic Polyimines

Abstract: Picosecond third harmonic generation (THG) spectroscopy in the range 0.9−2.4 μm (0.52−1.38 eV) and sum-over-states (SOS) theoretical modeling have been used to investigate the third-order nonlinear optical properties of a series of nine conjugated aromatic polyimines designed to elucidate structure−χ(3) relationships in conjugated polymers. The THG-measured frequency-dispersed third-order susceptibility (χ(3)) of the series of polymers has off-resonant and three-photon resonance-enhanced values in the ranges o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
23
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 103 publications
5
23
0
2
Order By: Relevance
“…Also, electronic and optoelectronic properties of these polymers depend on the π‐electron delocalization connected with chain planarity. A decrease of planarity lowers the HOMO level but raises the LUMO level and leads to a wider band gap 23–26…”
Section: Introductionmentioning
confidence: 99%
“…Also, electronic and optoelectronic properties of these polymers depend on the π‐electron delocalization connected with chain planarity. A decrease of planarity lowers the HOMO level but raises the LUMO level and leads to a wider band gap 23–26…”
Section: Introductionmentioning
confidence: 99%
“…Случайность связывания в процессе сополимеризации и асимметричность расположения боковых заместителей полимера может привести к значительному увеличению оптической нелинейности [153].…”
Section: нелинейно-оптические свойства полиазометиновunclassified
“…Singer K. и соавторы определили, что значение гиперполяризуемости первого порядка β 0 для азометина (23) составляет 3710 -30 esu, [159] Положение донорных и акцепторных групп в ядрах азометинов также имеют существенное влияние на значения , [153] что отображено в табл. 1.…”
Section: нелинейно-оптические свойства полиазометиновunclassified
“…Molecular engineering of chromophores has been one of the major pathways that has been exploited to achieve stronger nonlinear absorption [1,9,[11][12][13][14][15][16][17][18]. Recently we have shown that nonlinear absorption can also be enhanced via incorporation of nonlinear materials into multimode waveguides [2,19].…”
Section: Introductionmentioning
confidence: 99%